2014
DOI: 10.1038/pr.2014.129
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific association between infant diet and white matter integrity in 8-y-old children

Abstract: Background:The American Academy of Pediatrics recommends breastfeeding, which is well known to promote cognitive and behavioral development. The evidence for why this occurs is not well understood. Methods: Fifty-six 7.5-to 8.5-y-old healthy children were breastfed (BF; n = 22, 10 males) or formula-fed (FF; n = 34, 16 males) as infants. All children were administered: the Reynolds Intellectual Assessment Scale (RIAS); the Clinical Evaluation of Language Fundamentals (CELF-4) tests; and magnetic resonance imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 40 publications
3
36
2
1
Order By: Relevance
“…Results presented here extend previous findings of brain structural disparities in breast versus formula-fed children (Deoni, Dean, et al Ou et al, 2014) to cognitive differences, with suggestive negative associations between cognitive functioning and exclusive formula-feeding relative to breastfeeding, although these associations were insignificant after adjustment. Of note, no significant difference in cognition was found in association with mixed breast and formula feeding and exclusive breastfeeding, thus providing no evidence against the previously reported finding that even limited breastfeeding can positively influence early neurodevelopment relative to exclusive formula (Borra, Iacovou, & Sevilla, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…Results presented here extend previous findings of brain structural disparities in breast versus formula-fed children (Deoni, Dean, et al Ou et al, 2014) to cognitive differences, with suggestive negative associations between cognitive functioning and exclusive formula-feeding relative to breastfeeding, although these associations were insignificant after adjustment. Of note, no significant difference in cognition was found in association with mixed breast and formula feeding and exclusive breastfeeding, thus providing no evidence against the previously reported finding that even limited breastfeeding can positively influence early neurodevelopment relative to exclusive formula (Borra, Iacovou, & Sevilla, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…Several studies have used DTI to establish links between white matter diffusion parameters and early environment, showing that white matter structure in childhood is linked to socioemotional deprivation in early life, pre and post‐partum maternal depressive symptoms, and infant nutrition, i.e. breastfeeding, among numerous other examples. A key area of future research will be to investigate how these environmental factors alter trajectories of development with age.…”
Section: Factors Contributing To Varying Development Ratesmentioning
confidence: 99%
“…In full term infants, magnetic resonance imaging (MRI) of the brain demonstrated greater white matter development from 10 months to 4 years 11 and at 8 years 12 ; and greater cortical thickness in adolescence 13 in relation to early breastfeeding exposure. In preterm infants, one small study 14 (n=50) found positive correlations of breast milk intake with total brain volume at 15 years of age.…”
mentioning
confidence: 99%